2017
DOI: 10.1016/j.jnutbio.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to short-chain fatty acids modulates transport and metabolism of microbiome-derived phenolics in human intestinal cells

Abstract: Dietary fiber-derived short-chain fatty acids (SCFA) and phenolics produced by the gut microbiome have multiple effects on health. We have tested the hypothesis that long-term exposure to physiological concentrations of SCFA can affect the transport and metabolism of (poly)phenols by the intestinal epithelium using the Caco-2 cell model. Metabolites and conjugates of hesperetin (HT) and ferulic acid (FA), gut-derived from dietary hesperidin and chlorogenic acid, respectively, were quantified by LC-MS with auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…In this study, the placebo treatment consisted of cellulose, which can increase the production of SCFA . Recently, Van Rymenant et al . have demonstrated that SCFA alter in vitro bioavailability and phase II conjugation of hesperetin and ferulic acid in chronically pre‐treated Caco‐2 cell cultures, although in vivo studies supporting this observation are currently lacking.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, the placebo treatment consisted of cellulose, which can increase the production of SCFA . Recently, Van Rymenant et al . have demonstrated that SCFA alter in vitro bioavailability and phase II conjugation of hesperetin and ferulic acid in chronically pre‐treated Caco‐2 cell cultures, although in vivo studies supporting this observation are currently lacking.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, to elucidate the mechanisms of hesperidin conversion throughout the gastrointestinal tract, various batch and continuous luminal digestion models simulating enzymatic and microbial degradation were set up. In another in vitro approach, absorption and phase II metabolism of hesperetin in Caco‐2 cells as a model for the gut epithelium have also been studied extensively, and the impact of microbial fermentation products such as short chain fatty acids on hesperetin transport and phase II metabolism in Caco‐2 cells was recently demonstrated . Similar experiments for the microbial degradation products are however scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a Transwell insert also provides a robust strategy to form microbial-product gradients across intestinal epithelial monolayers; however, the vast majority of these studies have focused on the response of tumor cells to microbial metabolites. 128 , 129 , 130 , 131 Although these models provide useful insights, recently established primary intestinal epithelial monolayer cultures in these inserts are expected to replace the intestinal cancer models. 23 , 26 , 27 , 132 For example, a mouse primary colonic monolayer was used to show that interferon-γ (IFN-γ) did not increase IgA-receptor expression or transcytosis as IFN-γ did in tumor cells.…”
Section: Engineered In Vitro Gradientsmentioning
confidence: 99%
“…Four proteins belonging to the UDP‐glucuronosyltransferase isoforms (Ugt1a7c, Ugt1a6, Ugt1a1, and Ugt2b34) were all decreased in the PEP gavage group and annotated with the metabolism of toxic xenobiotics and endogenous compounds, along with the glucuronidation process. This would enhance the excretion of these compounds from the body and the decreased expressions might be due to the SCFAs concentrations increasing effects of PEP on the GIT contents …”
Section: Discussionmentioning
confidence: 99%